Selection of native isolates of Beauveria bassiana (Ascomycota, Hypocreales) for the control of the coffee borer beetle Hypothenemus hampei (Scolytinae) in Brazil - Dalvi, Leandro Pin; Pratissoli, Dirceu; Polanczyk, Ricardo Antonio [UNESP]; Andrade, Gilberto Santos (Adam Mickiewicz University Poznan, 2011)
Hypothenemus hampei (coffee borer beetle or coffee berry borer) is the main pest of coffee Coffea spp. in the world. The aim of this study was to select native isolates of the ascomycete Beauveria bassiana for biological control of this pest. We collected 27 isolates on H. hampei from the state of Espírito Santo in Brazil. Isolates CCA-UFES/Bb-15, Bb-11, Bb-4 and Bb-18 were selected, with confrmed beetle mortality of > 60% after spraying with a suspension of 105 conidia/mL. The median lethal concentration (LC50) of these isolates varied from 4.0 × 104 to 7.9 × 104 conidia/mL. The standard isolate (ESALQ-447) showed the highest conidiogenesis, with 8.5 × 106 conidia, followed by CCA-UFES/Bb-18, Bb-11, Bb-15 and Bb-4, all exceeding 4 × 106. Isolates CCA-UFES/Bb-4, Bb-11, Bb-15, and Bb-18 have a potential to control H. hampei.
Keywords: Biological control; Coffee; Conidiogenesis; Entomopathogenic fungus